LOW SERUM IRON LEVEL AND LYMPHOCYTE DNA DAMAGE AMONG ADULTS - Samal, Pinak; N., Suchetha Kumari; Samal, Indira R.; Sathish, Kathyayani (Journal of Health and Allied Sciences NU, 2012)
Cellular DNA damage has been related to both external and internal factors. Serum Iron is one of the factors which has importance in the oxidative status of the cell. Higher iron levels have been found to be associated with imbalance in the oxidation-antioxidant system and has been associated with DNA damage due to oxidative stress. However, oxidative stress and DNA damage has also been reported in iron deficiency states, in some studies. It appears that the body iron level should be maintained at optimum level for a balanced scenario and both iron excess as well as iron deficiency states may be associated with oxidative stress and attendant DNA damage. In this study, the blood collected from eighty four volunteers (fifty six males and twenty eight females) was subjected to estimation of serum iron (Bathophenanthroline method). Also, Lymphocyte DNA damage was ascertained by Alkaline Comet Assay method (Qualitative assessment only). The range of serum iron in this group was found to be between 39.91 μgm/dl – 93.55 μgm/dl in females and between 37.7 μgm/dl – 133.63 μgm/dl in males. Very high as well as very low serum iron was not found in this study group as the volunteers were all ambulatory and asymptomatic. Among the volunteers who had serum iron less than 50 μgm/dl(N=17), eleven (64.7%) had evidence of DNA damage as per the alkaline comet assay. Among the group having serum iron 51-70 μgm/dl (N=34), fourteen (41%), had evidence of DNA damage. Similarly, among the group, having serum iron 71-90 μgm/dl (N=27), evidence of DNA damage was seen in ten (37%) persons. There were very few persons with serum iron more than 91 μgm/dl (N= 6) and out of them two had evidence of DNA damage. In total, out of 84 persons, thirty seven (44%) had evidence of DNA damage as per alkaline comet assay. This trend of inverse dose response relationship was also noticed separately among males as well as in females. This is a preliminary exploratory study in India (although a few similar reports also exist in studies done in other parts of the world) and admittedly, had not taken into account of other confounding factors. Nevertheless, the findings suggesting association of low serum iron level and DNA damage, which has also been reported in some earlier studies at other parts of the world, need further examination through larger controlled studies.
Keywords: DNA damage; Serum Iron; Lymphocyte DNA; Iron Deficiency Anemia; Oxidative Stress; Mutagenesis